Shaping of the European Commission: Process and Outcome - Vladimir Schweizer (Научно-аналитический вестник Института Европы РАН, 2019)
The main events of this year in the life of the EU were the May elections to the European Parliament (EP) and the ongoing formation of the key executive authority of the EU – the European Commission (EC). The delay in the start of its work is connected with sharp disagreements among EU leaders both on procedural issues and on the personalities of candidates for EU top posts. The problem of reaching consensus between the members of the new triumvirate – Christian democrats, social democrats and liberals – as well as the personal agreements of E. Macron, A. Merkel, D. Tusk and J.-K. Juncker came to the fore. Brexit added urgency to solving the problem of renewing power teams, the constant postponement of which slowed down the process of starting work of EU power structures. Ultimately, by December 1, 2019, the EP by an absolute majority of votes approved the new composition of the EC.